The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1167/iovs.17-23213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 2% Rebamipide Eye Drops Related to Conjunctival Differentiation in Superoxide Dismutase-1 (Sod1) Knockout Mice

Abstract: Citation: Kojima T, Simsek C, Igarashi A, et al. The role of 2% rebamipide eye drops related to conjunctival differentiation in superoxide dismutase-1 (Sod1) knockout mice. Invest Ophthalmol Vis Sci. 2018;59:1675-1681. https://doi.org/10.1167/iovs.17-23213 PURPOSE. The superoxide dismutase-1 knockout (Sod1 À/À ) mouse is an age-related dry eye mouse model. We evaluated the role of 2% rebamipide ophthalmic solution on the conjunctiva and ocular surface alterations in Sod1 À/À mice. METHODS.Rebamipide eye drops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It has been reported that topical administration of rebamipide significantly improves symptoms, corneal fluorescein staining, conjunctival lissamine green staining, and tear film breakup time in DED. 7,10,17 Previous animal studies have shown that rebamipide instillation also improved ocular surface epithelial differentiation with a FIG. 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that topical administration of rebamipide significantly improves symptoms, corneal fluorescein staining, conjunctival lissamine green staining, and tear film breakup time in DED. 7,10,17 Previous animal studies have shown that rebamipide instillation also improved ocular surface epithelial differentiation with a FIG. 2.…”
Section: Resultsmentioning
confidence: 99%
“…*Represents P < 0.05, **Represents P < 0.01. reduction in keratinization. 10 Additionally, Kinoshita et al have shown that even short-term rebamipide instillation has favorable therapeutic effects on corneal staining scores. Moreover, they also have demonstrated that administration of rebamipide ophthalmic solution results in significant improvement in both the objective signs and subjective symptoms of DED.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effects of rebamipide eye drops on the ocular surface epithelium, tear function, and the conjunctiva have been investigated previously [14,15,20,21,22], its effects on corneal subbasal nerves have not yet been examined. Moreover, there is a paucity of studies which have evaluated rebamipide eye drops in VDT animal models.…”
Section: Introductionmentioning
confidence: 99%